Characterization of ALS-associated proteins in Saccharomyces cerevisiae - Ng, Qing Hao (Nanyang Technological University, 2021)
Various mutations in the low complexity domain of RNA-binding proteins such as TDP-43, FUS and hnRNPA1 have been identified from familial ALS (Amyotrophic Lateral Sclerosis) patients. Aggregation of these RNA-binding proteins, particularly TDP-43, is a hallmark of ALS. It is notable that these ALS-associated RNA-binding proteins can be sequestered in stress granules that form transiently during stress conditions. During aging, however, stress granules become chronic and thus, the retention time of RNA-binding proteins in stress granules becomes prolonged. Furthermore, the high local concentration of RNA-binding proteins can lead to their aggregation. In this project, I show that RNA-binding proteins can also be sequestered to processing bodies, another type of cytosolic ribonucleoprotein granule. I next asked if sequestration of TDP-43 in stress granules or processing bodies depends on its RNA-binding property. Surprisingly, mutations in RNA recognition motifs of TDP-43 resulted in the formation of perinuclear annular structures that did not colocalize with cytosolic ribonucleoprotein granules. Investigation of this unique structure is expected to shed light on the mechanism of TDP-43 aggregation.